2015
DOI: 10.1179/1743132815y.0000000050
|View full text |Cite
|
Sign up to set email alerts
|

Motor outcome of deep intracerebral haemorrhage in diffusion tensor imaging: comparison of data from different locations along the corticospinal tract

Abstract: Objectives: Although diffusion tensor imaging (DTI) is widely studied to assess the motor outcome after ischaemic stroke, there is paucity of data regarding outcomes of intracerebral haemorrhage (ICH). The aim of this study was to determine the DTI data from different locations along the corticospinal tract (CST) and association to motor outcome. Methods: We prospectively recruited patients with deep ICH admitted to our hospital from November 2010 to July 2012.Diffusion tensor imaging was performed within 14 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
1
17
0
1
Order By: Relevance
“…In addition, in the current study, the determination of the DTI data from different locations along the corticospinal tract (CST) pathway and association to the motor outcome of flow-up at 6 months reveals that the corona radiata and the posterior limb of the internal capsule might be the primary locations for predicting the long-term motor recovery. This finding is consistent with previous studies 16,20 . But most previous studies have used only several pointed ROIs included corona radiata, perihematomal edema area, cerebral peduncle, and pons, as the ROI for FA measurements to predict motor outcomes.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, in the current study, the determination of the DTI data from different locations along the corticospinal tract (CST) pathway and association to the motor outcome of flow-up at 6 months reveals that the corona radiata and the posterior limb of the internal capsule might be the primary locations for predicting the long-term motor recovery. This finding is consistent with previous studies 16,20 . But most previous studies have used only several pointed ROIs included corona radiata, perihematomal edema area, cerebral peduncle, and pons, as the ROI for FA measurements to predict motor outcomes.…”
Section: Discussionsupporting
confidence: 94%
“…Such damage to the whiter matter by acute haemorrhage in the basal ganglia region will change the integrity and spatial direction of axonal membranes and myelin sheath of the fibrous bundle, thereby affecting the water molecular diffusion barrier to increase the free diffusion of water molecules and decrease the diffusion anisotropy of white matter in lesions, ultimately leading to a decrease in the FA value 23 . Studies have also shown that the FA value near the hematoma area is affected by the magnetic susceptibility of hemosiderin deposition or mixed vasogenic and cytotoxic oedema 16,24 . The FA value in the bottom segments (8-20th point) along the CST of the injured side was significantly lower than the uninjured side, such segments close to cerebral peduncle that did not close the lesion position also likely attributed to the significantly lower FA value in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The CST, which consists of the internal capsule, the cerebral peduncle and pyramid tract, is one of the most prominent pathways related to motor functional outcome after ICH (Liang et al, 2013 ; Venkatasubramanian et al, 2013 ; Cheng et al, 2015 ). The application of DTI for detecting CST injury after hemorrhagic stroke has been recently reviewed with a particular focus on the predictive value of DTI in ICH (Chaudhary et al, 2015 ).…”
Section: Detection Of Wmi After Ich Using Advanced Mri Techniquesmentioning
confidence: 99%
“…Інсульт є однією з головних причин інвалідності [1]. Пошкодження мозку позначається на структурі і функції периферичних нервів [2]. Відомо, що нейропатію серединного, литкового або сідничного нерва відмічають з 6-14-го місяця з часу розвитку захворювання [3,4].…”
Section: вступunclassified